The Principle of Responsibility to Protect: Its Significance and Implementation In Israel-Palestine Conflict - Aulawi, Muhammad Haris; Sherliana, Ade (Faculty of Law, Universitas Jambi, 2025)
This article explores the importance of the role of the principle of responsibility to protect of the UN in resolving the Israel-Palestine conflict by evaluating the international legal norms, the intervention of the international community, and the UN resolutions, as well as diplomatic initiatives as an effort to protect civilians in the midst of conflict. Relying on normative legal research methods, this research focuses on doctrinal analysis of relevant international legal principles that combine positivism and constructivism. This article utilizes primary and secondary data, such as UN reports, books, journal articles, and literature from the internet as a source to enrich this research. The study found that the principle of responsibility to protect has the potential to foster more effective protection for civilians in the midst of the Israel-Palestine conflict and is the basis for international intervention when a state fails to fulfil its responsibilities. However, the implementation of R2P faces a variety of challenges, including political bottlenecks in the UN Security Council, concerns over violations of state sovereignty, as well as a lack of global agreement on collective action. This article concludes that the application of the R2P principle by the United Nations to the Israel-Palestine conflict is urgent to prevent further escalation of violence. This article suggests reforms in UN mechanisms and strong international political support to ensure the successful application of these principles to address the issue.